Wellness tourism: unmet human need development management level perspectives from wellness retreats in sri lanka - Perera, L.A.P.C.; Balasooriya, B.L.P.C.; Wanathunga, A.I.; Suraweera, S.A.D.P.S. (University of Jaffna, 2022)
Purpose: Wellness as a lifestyle refers to a spatial state of health, incorporating the harmony of body, mind and spirit. To diver the best quality wellness experience to the guests, the staff engaged in the wellness industry plays the major role. Though the employees are satisfied, they still have unmet human needs to be developed. This paper is designed to outline those unmet needs and to identify the possible strategies that can be proposed. Methodology: This study focuses on outlining the unmet human needs of workers in the Wellness Retreats in Sri Lanka while identifying the possible strategies that can be taken to meet the unmet needs of employees. In order to achieve the objectives of the study ten Wellness Retreat centers were selected as the sample and interviewed, employing judgmental sampling. The research is based on qualitative design and analyzed using thematic analysis. A detailed analysis was applied to narrate the answers given by the respondents using three sub themes as: Vocational Training Needs, Soft Skills Needs and Social Recognition Needs. Findings: The study identified Human Development Needs as the parental theme and Vocational Training Needs, Soft Skills Needs and Social Recognition Needs as the sub themes. The employees highlights their vocational training needs as their most and foremost unmet needs. Basics on wellness and Aurvedic therapy, foreign language knowledge, online and physical training opportunities, institutional level course on theoretical and physical learning, knowledge on cosmetology treatment practices, national institute to give industry recognized certificates, vocational training on beauty, therapy and acupuncture handling, health dietary planning, vocational training diplomas or NVQ level programs were emphasized by them. They emphasize the way to become SMART employee, diplomatic nature, and emotional intelligence, especially on the self-disciplines. Research Limitations: The main limitation was the difficulty to diagnosis employees attributed to health and wellness sector especially due to limited numbers of health and wellness retreats in Sri Lanka. Their reluctant to express their true feelings due to job security was another limitation. Implications: Workers in the wellness sector demand for diplomas or NVQ level certification. Providing a certification will add value to the person as well to the industry. This can be highlighted as one of the practical implications of this research work. The authors need to highlight the necessity of providing them with a valid license certificate. The study mainly relies upon positive implications to both managerial levels and socioeconomic aspects. The management can decide what type of cognitive changes that needs to implement to meet the unmet needs of their employees. Accordingly, they can decide what humanistic learning theory and behavioral theories that could be adopted to meet the unmet employee needs. As well, self-efficacy of the employees will boom and dignity and pride based on the job satisfaction can be assured.
Keywords: Human needs; Social recognition; Spa; Wellness tourism